A Gold Micro-Reference Electrode for Impedance and Potential Measurements in Lithium Ion Batteries. Issue 10 (19th August 2016) - Solchenbach, Sophie; Pritzl, Daniel; Kong, Edmund Jia Yi; Landesfeind, Johannes; Gasteiger, Hubert A.
Abstract : Impedance measurements of lithium-ion batteries are a powerful tool to investigate the electrolyte/electrode interface. To separate the contributions of anode and cathode to the full-cell impedance, a reference electrode is required. However, if the reference electrode is placed inappropriately, the impedance response can easily be biased and lead to erroneous conclusions. In this study, we present a novel micro-reference electrode for Swagelok-type T-cells which is suitable for long-term impedance and reference potential measurements. The reference electrode consists of a thin insulated gold wire, which is placed centrally between cathode and anode and is in-situ electrochemically alloyed with lithium. The resulting lithium-gold alloy reference electrode shows remarkable stability (>500 h) even during cycling or at elevated temperatures (40°C). The accuracy of impedance measurements with this novel reference electrode is carefully validated. Further, we investigate the effect of different vinylene carbonate (VC) contents in the electrolyte on the charge transfer resistance of LFP/graphite full cells and demonstrate that the ratio of VC to active material, rather than the VC concentration, determines the impedance of the anode SEI.